Boutique hotels the history of becoming popular - Hidzhelitska, Olga; Гіджеліцька, Ольга Степанівна (My University, 2013)
Today, a traveler needs a place to work comfortably and get a good night's sleep. As a result, hotels are becoming domestic, and the more historic a property is, the better suited it is to become intimate and cozy. Besides, travelers nowadays expect more than simply comfort and convenience. An increasing number of travelers prefer to be positively "surprised". When planning trips, they seek properties that are noticeably different in look and feel like branded hotels. That’s why boutique hotels are becoming more and more popular all over the world.
Keywords: готелі; бутік-готелі; історія; отели; бутик-отели; история; hotels; boutique hotels; history; кафедра туристичного та готельного бізнесу